The Influence of the Deep Learning Approach from the Constructivism Approach Perspective on Biographical Text Writing Skills - Winda Simbolon; Monalisa Frince Sianturi; Sarma Panggabean (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The constructivist-based deep learning approach is a learning approach that prioritizes high-level thinking skills through an inductive model that is believed to be able to achieve learning objectives. This study aims to determine: 1) the pre-test results of biographical text writing skills; 2) the post-test results of biographical text writing skills; 3) the effect of implementing a constructivist-based deep learning approach on biographical text writing skills. This study uses a quantitative method with a quasi-experimental design in the form of a one-group pretest-posttest design. The study took place at SMK Telkom 1 Medan in the 2025/2026 academic year. The population of this study was 32 students of class X RPL 2 SMK Telkom 1 Medan who participated in the pre-posttest and learning activities of biographical text writing skills using a constructivist-based deep learning approach. The research sample was 30 students determined based on a statistical formula. The instrument used was a biographical text writing skills test that was compiled using systematic and objective procedures to produce test specifications as a basis for compiling the test. The research data were analyzed using a paired sample t-test. The results of the study showed: 1) the mean pre-test of biographical text writing skills was 48.23 (very poor category); 2) the mean post-test of biographical text writing skills was 84.6 (very good category); 3) the application of a deep learning approach based on a constructivist approach had a significant effect on biographical text writing skills.